Substance use among university students in sanliurfa - Altındağ, Abdurrahman; Yanık, Medaim; Yengil, Erhan; Karazeybek, Akif Himmet (Journal of Dependence, 2005)
Objective: The objective of this study was to estimate the extent and nature of substance use among university students in Sanliurfa. Methods: Using an anonymous, self-administered questionnaire, we surveyed 253 first-year students of Sanliurfa Harran University in 2004-2005 academic year. The study group consisted of 27 students from Faculty of Medicine and 226 students from Faculty of Arts and Sciences. The average age of the students was 20.6 years [standard deviation (SD) = 1.7], with 171 students (68%) being male. Results: The overall prevalences of lifetime cigarette smoking, alcohol use and illicit drug use were 64.4, 30.4 and 2.3%, respectively. There was no significant difference in smoking between medical and arts-sciences students. Male students were more likely to smoke than females. There was no significant difference in drinking alcohol between medical and arts-sciences students. There was no gender difference in drinking alcohol in either group. Peer use of alcohol was the predictor of using alcohol among university students. Conclusion: The profile of university students’ substance use suggested by this survey is: high smoking rates, considerably common use of alcohol and rare use of illicit drugs. More research is needed to identify and understand the factors leading university students from drug use to abuse or dependence.